Shaping perception through metaphor: a study of Churchill’s political language - Karimova Ominaxon Maxmudovna; Arustamyan Y. Y (Academia One, 2025)
This article explores the central role of metaphor in political discourse through the lens of Conceptual Metaphor Theory (CMT), originally developed by George Lakoff and Mark Johnson. It argues that metaphors are not merely ornamental devices, but fundamental cognitive tools that structure human thought, influence public perception, and shape socio-political ideologies. The study categorizes political metaphors into structural, ontological, and orientational types, each performing distinct cognitive and rhetorical functions. Using detailed analyses of Winston Churchill’s speeches: “We Shall Fight on the Beaches” (1940) and “The Sinews of Peace” (1946), the article illustrates how metaphors frame war, peace, leadership, and crisis through familiar experiential domains. Structural metaphors transform abstract political events into comprehensible constructs like machines, journeys, or buildings, while ontological metaphors embody concepts such as war, peace, or responsibility, enhancing their emotional and persuasive power. Orientational metaphors organize political hierarchies and moral positions using spatial schemas. The findings demonstrate that metaphorical language in Churchill’s speeches strategically shapes public understanding and emotional response, reflecting the ideological, cultural, and historical contexts of their time. Ultimately, the article affirms that metaphors are indispensable not only to rhetoric but to cognition, positioning them as essential instruments in political communication and collective meaning-making
Keywords: Conceptual Metaphor Theory; political discourse; structural metaphors